CONTENT AND COGNITIVE DEPTH IN TEACHING OF SOCIAL AND CIVIC STUDY AREA - Ozoliņa, Liene; Kļaviņa, Aija; Namsone, Dace (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2023)
Research problem - in Latvia from 2016 started Curriculum Development and Implementation project. For Social and civic study area (SCSA) subject context it means fundamental changes –social constructivist approach in teaching as well as new subjects and study courses were implemented.The research aim is to analyse clarity of the chosen content, cognitive activity (development of deeper thinking) and historical thinking concepts (HTC) in observed lessons (N=16) of SCS area subjects to preliminary define implementation outcomes of educational reform.In this research the authors wish to clarify:RQ1 How do teachers succeed in integrating the offered learning content and opportunities to delve into it in SCSA lessons?RQ 2 How is it possible to determine the extent to which teachers succeed in offering students the opportunity to develop historical thinking abilities in SCSA subjects?The primary method used was lesson study using lesson analysis rubric developed and previously validated by Interdisciplinary Centre for Educational Innovation (University of Latvia). Observed lessons took place in seven schools in different municipalities at the first semester of academic year 2022 - 2023.It was concluded that HTC are partially evident in observed lessons and the cognitive depth differs.